2012
DOI: 10.4103/0974-2700.99687
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric emergency medical services and their drawbacks

Abstract: Aim:To survey the literature on Pediatric Emergency Medical Services (PEMS) with an aim to focus its drawbacks and emphasize the means of improvement.Materials and Methods:Published articles selected for inclusion were based on the significance and understanding of literature search on different aspects of PEMS. To meet this criterion, PubMed, PubMed Central, Science Direct, Uptodate, Med Line, comprehensive databases, Cochrane library and the Internet (Google, Yahoo) were thoroughly searched.Results:PEMS prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The majority of the respondents (n=63, 43.4%) indicated that the combined neonatal theory hours and practical hours during their training had been inadequate to prepare them to deal with critically ill neonates.This corroborates findings from a study conducted in South Africa by Moodley who reported that paramedic graduates felt ill prepared for independent practice due to clinical practice learning objectives not being adequately achieved, also questioning the quality of that care provided by such EMS personnel as a result of this pitfall (10). The infrequency which ALS providers clinically manage critically ill neonates may inadvertently impact negatively on their level of confidence and technical neonatal skill performance when they are eventually called on to resuscitate a sick neonate (11). The current study reports that only a small group of respondents (n=5; 3.4%) had been exposed to managing critically ill neonates on a daily basis; these are mainly from the neonatal intensive care unit ambulances.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The majority of the respondents (n=63, 43.4%) indicated that the combined neonatal theory hours and practical hours during their training had been inadequate to prepare them to deal with critically ill neonates.This corroborates findings from a study conducted in South Africa by Moodley who reported that paramedic graduates felt ill prepared for independent practice due to clinical practice learning objectives not being adequately achieved, also questioning the quality of that care provided by such EMS personnel as a result of this pitfall (10). The infrequency which ALS providers clinically manage critically ill neonates may inadvertently impact negatively on their level of confidence and technical neonatal skill performance when they are eventually called on to resuscitate a sick neonate (11). The current study reports that only a small group of respondents (n=5; 3.4%) had been exposed to managing critically ill neonates on a daily basis; these are mainly from the neonatal intensive care unit ambulances.…”
Section: Discussionmentioning
confidence: 84%
“…Ismail: Intensive care for neonatal interfacility transfers: Preparedness of ALS providers Australasian Journal of Paramedicine: 2020;17 manage critically ill neonates may inadvertently impact negatively on their level of confidence and technical neonatal skill performance when they are eventually called on to resuscitate a sick neonate (11). The current study reports that only a small group of respondents (n=5; 3.4%) had been exposed to managing critically ill neonates on a daily basis; these are mainly from the neonatal intensive care unit ambulances.…”
Section: 1mentioning
confidence: 99%
“…These results may raise concerns and needs for pediatric care at the ED as pediatric patients require specific narrow doses and therapeutic ranges of medication. 9,12 Regarding pediatric resuscitation, the causes were different among centers. In this study, respiratory disease was the leading cause as in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…An emergency medical service (EMS) is a service providing outof-hospital acute care and transport to definitive care, to patients with illnesses and injuries which the patient believes constitute a medical emergency. EMS encompasses many areas of emergency care, including the triage, evaluation, management, and transport of patients from the scene of an injury or illness to their arrival at an emergency care facility (the out-of-hospital or pre-hospital care), as well as the management within the emergency department (ED) [1,2].…”
Section: Introductionmentioning
confidence: 99%